EDUKASI PENCEGAHAN DAN PENANGANAN STUNTING PADA BALITA - Yuniske Penyami; Muhammad Faris Khilmi; Dewi Oktavianita; Tiara Arsi Hayunda; Triyani Puji Astuti; Khansa Aufanida Inayah; Gina Hadi Afifah; Salam Abdurrouf; Gisnaya Faridhotul Avisah; Citra Ningrum; Desiwi Nur Arifah Putri; Azki Khilmi; Wafiq Azzahra (Jurnal LENTERA, 2026)
Background: Stunting remains a chronic nutritional issue requiring a multi-professional approach. The stunting prevalence in Pekalongan City is recorded at 18.7%, which is still above the national target of 14%. This community service activity aims to provide education on the prevention and management of stunting among children under five in the working area of ​​the Jenggot Community Health Center (Puskesmas), Pekalongan City. Methods: This activity employed educational and mentoring methods utilizing an interprofessional collaborative approach during the planning stage. The target participants were five families with stunted children under five, selected based on recommendations from the community health center. Data were collected through family assessments, questionnaires regarding knowledge, parenting practices, and dietary habits, as well as anthropometric measurements and Z-score calculations. Interventions were implemented through interprofessional collaboration involving nurses, physicians, and nutritionists. Activities included education, demonstrations on preparing nutritious food, parenting guidance, and evaluation. Results:The average family knowledge score increased from 58 (pre-test) to 90 (post-test). Family parenting practices improved from the “sometimes” category to “often,” while children's dietary habits improved through increased dietary variety and animal protein intake. Conclusion: Education on stunting prevention and management improved family knowledge, parenting practices, and dietary habits. Interprofessional collaboration among health professionals facilitated more comprehensive, integrated, and sustainable interventions for preventing and managing stunting in children under five.